Perfectionism related to self-reported insomnia severity, but not when controlled for stress and emotion regulation - Br (Dove Medical Press, 2015)
Serge Brand,1,2 Roumen Kirov,3 Nadeem Kalak,1 Markus Gerber,2 Uwe Pühse,2 Sakari Lemola,4 Christoph U Correll,5 Samuele Cortese,6–8 Till Meyer,1 Edith Holsboer-Trachsler1 1Psychiatric Clinics of the University of Basel, Center for Affective, Stress and Sleep Disorders (ZASS), Basel, Switzerland; 2Department of Sport, Exercise and Health, Division of Sport Science, University of Basel, Basel, Switzerland; 3Institute of Neurobiology, Bulgarian Academy of Sciences, Sofia, Bulgaria; 4Faculty of Psychology, University of Basel, Basel, Switzerland; 5Division of Psychiatric Research, North Shore – Long Island Jewish Health System, Zucker Hillside Hospital, NY, USA; 6School of Medicine, University of Nottingham UK; 7Centre for ADHD and Neuro-developmental Disorders Across Lifespan, Institute of Mental Health, University of Nottingham UK; 8New York University Child Study Centre, New York, NY, USA Background: Perfectionism is understood as a set of personality traits such as unrealistically high and rigid standards for performance, fear of failure, and excessive self-criticism. Previous studies showed a direct association between increased perfectionism and poor sleep, though without taking into account possible mediating factors. Here, we tested the hypothesis that perfectionism was directly associated with poor sleep, and that this association collapsed, if mediating factors such as stress and poor emotion regulation were taken into account. Methods: Three hundred and forty six young adult students (M=23.87 years) completed questionnaires relating to perfectionism traits, sleep, and psychological functioning such as stress perception, coping with stress, emotion regulation, and mental toughness. Results: Perfectionism was directly associated with poor sleep and poor psychological functioning. When stress, poor coping, and poor emotion regulation were entered in the equation, perfectionism traits no longer contributed substantively to the explanation of poor sleep. Conclusion: Though perfectionism traits seem associated with poor sleep, the direct role of such traits seemed small, when mediating factors such as stress perception and emotion regulation were taken into account. Keywords: perfectionism, perceived stress, emotion regulation, young adults, sleep quality